RESEARCH AND DEVELOPMENT OF THE PROCESS OF FORMATION OF A REGIONAL CYBERINFRASTRUCTURE ON THE BASIS OF LAMBDA-GRID TECHNOLOGIES - Masich, G.F.; Masich, A.G.; Stepanov, R.A.; Sukhanovskii, A.N.; Bobrov, A.V.; Chugunov, D.P.; Tiron, G.G.; Fayzrakhmanov, R.A.; Shchapov, V.A. (Perm Federal Research Centre Journal, 2015)
The paper provides information about the cyberinfrastructure created in the Urals that is designed to use all of the improvements in the field of high performance computing and consists of high-speed integrated optical network calculators, data storage systems and installations. The paper shows the problems of the organization of connections between end systems for high-speed extended communication lines and solutions to them through parallelism of their compounds. Particular attention is paid to the architectural solution that involves processing intensive flow of experimental data on a remote supercomputer in real time, demonstrating fundamentally new opportunities for experimental studies.